Hybrid systems in buildings: Control strategies for optimal integration - i-Tagba, Abdoul-Razak Al; Baneto, Mazabalo; Takshi, Arash; Lu-cache, Dumitru Dorin (Edelweiss Applied Science and Technology, 2025)
This study proposes an optimized control strategy for a hybrid photovoltaic–wind system with battery storage, designed for off-grid applications. The objective is to enhance energy stability and overall efficiency through an adaptive fuzzy logic-based MPPT controller. The methodological approach is based on multi-component modeling using MATLAB/Simulink, integrating a multi-port DC converter and parametric optimization functions. The results demonstrate an overall energy efficiency of 92.7%, a 22% reduction in power oscillations compared to the conventional P&O algorithm, and DC bus voltage stabilization within ±0.5%. Furthermore, power supply continuity reaches 98.7%, and total harmonic distortion remains below 3.2%. The hierarchical energy management strategy ensures that the battery state of charge is maintained between 30% and 90%. These performance outcomes suggest that the proposed architecture is well-suited for autonomous microgrids in remote areas. Practical implications include the optimization of hybrid systems for sustainable electrification.